Strategy for Developing Teacher Competence in Qur'anic Education Garden in The Modern Era: Analysis of Understanding of Tajweed At-Tadzkir Teaching Content - Tazkirah, Siti; Ilham, Ilham; Nasaruddin, Nasaruddin (Sekolah Tinggi Agam Islam Sumatera Medan, 2025)
The teaching of tajweed is a fundamental part of Qur'an education because it plays an important role in the accuracy and beauty of recitation. In the modern era, teachers' competence in understanding and teaching tajweed greatly determines the success of the learning process. This study aims to describe the implementation of the At-Tadzkir tajweed material at the Al-Qur'an Education Center in Bima City, identify the challenges faced by teachers in its implementation, and analyze the contribution of the material to the development of teachers' competencies. This study employs a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. The results of the study indicate that the At-Tadzkir material has been implemented gradually in several Quran Education Centers, with a focus on understanding the basic rules of tajweed recitation. The challenges faced include limited training time, insufficient class hours, lack of learning materials, and diverse educational backgrounds of the teachers. Despite these challenges, the implementation of this material has had a positive impact on improving teachers' understanding and practical skills in tajweed, as well as supporting strategies for the sustainable development of teachers' competencies in Qur'an education.